SISTEM INFORMASI ALUMNI SMP N 1 DAYUN MENGGUNAKAN FRAMEWORK LARAVEL DI KAB. SIAK - Anita Febriani; Wahyu Linda Wati; Hendry Fonda (Jurnal Ilmu Komputer, 2020)
Alumni data is one example of an information system designed to be able to help the work of an agency or company both in processing data to provide complete data through the availability of information services. Similarly, SMP N 1 Dayun which has approximately 5800 alumni and forms a large family bond of alumni which has a vision of realizing the extended family ties of SMP N 1 Dayun as an alumni institution that can accommodate the aspirations of its members and can contribute to the development of the quality of education as school partners. But the alumni data management system that still uses printed documents, resulted in data management that cannot be done effectively and efficiently, and writing errors often occur, it is difficult to find alumni data that has been damaged, and the data is difficult to update because information about alumni can only be accessed through grupchat on social media, whatsapp. With this problem the researcher raised the title of the thesis that is Alumni Information System of SMP N 1 Dayun Using Laravel Framework in Kab. Siak The design of this information system uses usecase diagrams, activity diagrams, class diagrams. Application of the waterfall method as a system development process. Using the programming language Framework Laravel, PHP and MySQL as a database. This information system is expected to help the school and alumni of SMP N 1 Dayun in managing data and as a bridge of hospitality.